THE ROLE OF REGIONAL HOUSE OF REPRESENTATIVES IN CARRYING OUT GOOD GOVERNMENT (GOOD GOVERNANCE) IN REGIONAL AUTONOMY ERA - Tamrin Muchsin; Jamiat Akadol; Karman (Journal of Islamic, Social, Economics and Development, 2020)
Giving services to community is one of obvious form of public service that receives serious attention from various groups, both practitioners, academics, and observers of public services and issues of injustice due to its complicated procedures, convoluted, old, wasteful, inefficient and annoying. By the existence of the role of Regional House of Representatives as a symbol of democracy in the region, which is institutionally as a representation of sovereign people, in reality it is powerless to face the executives.